Impact and Challenges of Western Medical Practice in Wukari Division 1926-1960 - Tatah Solange Kidzeru; Dada Joel Patrick; Tanko Angyetsokwa Adihikon; Dada Adebusola Olorunfemi; Yaro Kpendwa Daudu (African Journal of Medicine, Surgery and Public Health Research, 2026)
Health constituted a major concern in colonial Wukari Division, particularly because tropical diseases such as malaria and yellow fever contributed to high mortality among Europeans in West Africa. This study examines the impact and challenges of Western medical practice in Wukari Division from 1926 to 1960. The study adopted an empirical historical approach, drawing on primary and secondary sources to analyze the development of colonial healthcare services and their social implications. The findings indicate that Western medical practice contributed to technological advancement, sanitary and preventive services, and the introduction of clean pipe-borne water in Wukari Division. The study also reveals that the colonial government and missionary organizations played a significant role in shaping the health landscape of the area during the period under review. Before Nigeria’s independence in 1960, efforts were made to train African doctors, nurses, and other medical personnel, who later assumed responsibility for managing health institutions previously administered by European colonial and missionary personnel. However, Western medical practice in Wukari Division faced several challenges, including epidemics and disease outbreaks, cultural resistance, unequal distribution of medical resources, and administrative limitations. The study concludes that although colonial and missionary medical interventions contributed to the institutionalization of modern healthcare in Wukari Division, persistent structural and social challenges limited their effectiveness. It recommends deliberate policy and institutional actions to improve health services in the local government areas that formerly constituted Wukari Division.